A conceptual study on the awareness of food borne disease and food handling regulation among food handlers / Nor Raihana Asmar Mohd Noor ... [et al.] - Mohd Noor, Nor Raihana Asmar; Kamarul Zaman, Liziana; Yaacob, Norhayati; Hassan, Muhammad Syafiq (2021)
Good public health is one of the main concerns of the government. Most Malaysian love to eat, but how many of them concern the hygiene of the food? In Malaysia, the limitation of time for most people to prepare meals for themselves has increased the demand for food consumption from various food service establishments, and it has also become a trend for most Malaysian to eat out (Noraziah & Mohd, 2012). However, some food premises neglect the importance of hygiene and sanitation and thus, increase the risk of foodborne illness among the consumers. Unfortunately, these cases have always been neglected because most of the incidents were not reported to the enforcement authorities (Soon, Singh, & Baines, 2011). In a comprehensive study by New et al. (2017), most of the business or restaurant owners hire migrant food handlers from underdeveloped countries. The level of hygiene is questionable because usually, the migrant workers are not well trained in hygiene. Due to that, comprehensive food premises inspection must be done regularly to increase food safety awareness among the food owners and food handlers (Salleh, Wani, Abdullah, Chilek, & Hassan, 2017). Most of the studies on food-borne disease have analysed, knowledge, attitudes, and practice among food handlers (Soon et al., 2020; Nur Izyan et al., 2019; Isoni et al., 2019). Thus, to fill in the gap of the previous studies, this paper proposes to measure the level of awareness of the foodborne disease and food handling regulation among food handlers in Malaysia and to identify whether the awareness of foodborne disease predicts the adoption of food handling regulation among food handlers in Malaysia by using knowledge, attitudes, and practices in Kelantan, Malaysia.